Avaliação dos aspectos culturais, psicológicos e sociais que interferem no comportamento de risco de jovens homossexuais em relação ao HIV/AIDS. - Gouveia, Tiago Borges (2013)
In the last 12 years there has been a considerable increase in notifications of AIDS cases in the category of men who have sex with men, especially among those who are in the age group 15 to 24 years, according to data from the Ministry of Health. This study seeks to evaluate the cultural, psychological and social factors that affect the risk behavior among young gay people between 18 and 24 years old. The theoretical and methodological proposal chosen for the study was a qualitative approach, justified by the complexity of the object and its peculiarities intertwined, such as the relationship between the individual and society, the structure of the subject with beliefs, values, meanings, and how they relate with the social history process. We interviewed 10 youngsters and by triangulating the theoretical framework that emerged with the axes of the material collected, we understand the social representations of young people in relation to HIV and sexuality, to list situations, practices and behaviors they consider safe for their sexuality and find what the impact of policies to prevent these young people is. The results show that all individuals feel vulnerable to HIV and point out that the way of life and subjectivity of gays in this age group would be one of the factors that affects the risk behavior. About the prevention campaigns, it has been reported that they may have a role in warning, but not decisively, since awareness actually only occurs when there is contact with the disease in a concrete way, either after a risky behavior or through close people who have been contaminated.